Influência do resfriamento dinâmico na medição da tensão limite de escoamento - Apenburg, Bárbara Pessini Penna Forte (2015)
Non-Newtonian fluids may present several complex characteristics, such as viscoelasticity, plasticity and thixotropy. Understanding the behaviour of these materials is essential to facilitate its applicability, since many of them are present in daily life, such as gels, chocolate, and mayonnaise. The material studied on the present work was an waxy crude oil. The oil, present in reservoirs located in deep water, when subjected to low temperatures during production shutdowns, precipitates its paraffin, creating a structure which may be very resistant to flow. Thus, the formed material may represent a great difficulty to production restart. The design of pumps and compressors used in these systems depend on a rheological property called yield stress and therefore, it is essential to obtain reliable values of this rheological parameter. However, the complex behaviour, and the dependence of the crude oil characteristics on the shearing and temperature history make this a challenging task. Besides these, other factors may influence the measurement of yield stress, as the effect of wall slip and if the cooling is static or dynamic. This work shows the variation of yield stress for tests with dynamic cooling. The imposition of a stress during cooling caused the reduction in yield stress 0. Increasing the imposed stress, 0 decreased until it reached a minimum. Next, it was noticed an increase in yield stress with increasing imposed stress. The experiments carried out in this work were made in a commercial stress control rheometer. The effect of wall slip was tested by comparing smooth and rough geometries and it was verified signs of its presence, with the reduction of yield stress for smooth geometries. The equation of Weissenberg-Rabinowitsch, used for correction of the inhomogeneity of the shear stress along the radius geometry, seemed to be not necessary for the demonstrated results.